Decarbonisation of energy: Determining a robust mix of energy carriers for a carbon-neutral EU - Georg Zachmann; Franziska Holz; Alexander Roth; Ben McWilliams; Robin Sogalla; Frank Meißner; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
[Key Findings] The Fit for 55 package foresees a significant speeding up of European decarbonisation. This requires many new and upgraded policy frameworks. The European Commission has already proposed extensive reforms to the EU's energy and climate policy framework, and more are forthcoming before the end of 2021. The purpose of this report is to provide insight into the rationale behind these revisions. Spe-cifically, this is done by informing policymakers about the implications of different fuel mixes in a decarbonised EU in 2050. We explore three scenarios with differing demand assumptions for electricity, hydrogen and alternative green gases.
Keywords: 330